Beam test of a one-dimensional position sensitive chamber on synchrotron radiation - 刘梅 代洪亮 祁辉荣 庄保安 张建 刘荣光 朱启明 欧阳群 陈元柏 江晓山 王雅洁 刘鹏 常广才 (Chinese physics C, 2013)
A one-dimensional single-wire chamber was developed to provide high position resolution for powder diffraction experiments with synchrotron radiation. A diffraction test using the sample of SiO2 has been accomplished at 1W2B laboratory of Beijing Synchrotron Radiation Source. The data of the beam test were analyzed and some diffraction angles were obtained. The experimental results were in good agreement with standard data from ICDD powder diffraction file. The precision of diffraction angles was 1% to 4.7%. Most of the relative errors between measured values of diffraction angles and existing data were less than 1%. As for the detector, the best position resolution in the test was 138 p.m （a value） with an X-ray tube. Finally, discussions of the results were given. The major factor that affected the precision of measurement was deviation from the flat structure of the detector. The effect was analyzed and the conclusion was reached that it would be the optimal measurement scheme when the distance between the powder sample and detector was from 400 mm to 600 mm.